Gas Hydrate Inhibitors - Khan, M.S. (Springer Verlag, 2020)
This chapter discusses the current focus on reported literature for gas hydrate inhibitors. The fundamental concepts on gas hydrate formation and its applications are also primarily presented briefly. The limitations of commercial gas hydrate inhibitors and the need for new inhibitors have been also discussed. This brief review can provide a roadmap to the future for research directions in the search for an ideal gas hydrate inhibitor. Â© 2020, Springer Nature Switzerland AG.